Generic Specificity of Nikolai Kolyada’s Play "Baba Chanel" (2010) - Zyśk, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article is dedicated to the study of distinct features of Nikolai Kolyada’s play Baba Chanel [The Hag Chanel], with the view to defining the piece’s genre. The author, referencing work of other scholars, pays attention to the types of characters, the topic, the language and the presence of the author in the play. Moreover, the conflict between the characters and the world is described. A substantial part of the article is devoted to showing the features which are characteristic of reportage, in line with Iakov Zharski’s research. The article ends with a summary of the study and with the presentation of Baba Chanel’s generic specificity: this takes into account the features discussed and the authorial definition.